SALT CONTENT OF SEAWATER AND ICE (SOLEVOI SOSTAV MORSKOI VODY I LDA) - Blinov,L. K. (1968)
The paper represents two chapters of an unfinished book 'Chemistry of the Sea.' It discusses the salt content of ocean water, salinity and salt composition of sea ice in connection with the processes of transitional stages, and the formation of ice from seawater as a complex solution. The study is based on a large quantity of factual material and presents interesting and original conclusions. (Author) Trans. of Gosudarstvennyi Okeanograficheskii Institut. Trudy (USSR) v83 p5-55 1965, by M. Slessers.